Perlindungan Hukum Pekerja yang Terkena Pemutusan Hubungan Kerja (PHK) untuk Mengambil Jaminan Hari Tua (JHT) Sebelum Berusia 56 Tahun dalam Permenaker 2/2022 - Mahayoni Mahayoni; Soraya Dewi Kartikasari (Problematika Hukum, 2019)
Social security is a crucial thing that everyone must have, as this has been regulated and guaranteed by the state, and the state has an obligation to fulfill the rights of these citizens. In connection with this matter, the Indonesian government has regulations regarding social security regulated in Law No. 40/2004 concerning the National Social Security System, including health insurance, work accident insurance, death security, and one that will be concern of discussion in this research is a program regarding Pension Security or commonly called Jamaican Hari Tua (JHT). The regulations regarding this matter have changed several times, but still aim to focus on ensuring that Indonesian citizens who are the JHT participants can enjoy a decent life after entering retirement. Provisions for disbursing funds for participants have changed from the initial regulations to the updated regulations, for example changes to implementing regulations regarding the JHT, namely the Ministerial Regulation of Manpower No 2/2022 concerning "Procedures and Payment of Pension Security", one of the problems that arises is regarding the conditions for disbursing the JHT funds especially by participants affected by Termination of Employment or commonly called Pemutusan Hubungan Kerja (PHK) different from the previous Ministerial Regulation of Manpower, which did not require the age of participants who were affected by the layoffs. This raises the pros and cons in society. This research focuses on protection for the JHT participants who are laid off before they are 56 (fifty six) years old, so they can withdraw the JHT contributions that have been paid, thus achieving the goal of Law No. 40/2004 to ensure people's lives.